Vertical jump improvement in elite swimmers following 8 weeks training with 'strength' shoes - Reneau, P.; Martino, M.; Smith, J.; Richardson, M.; Bishop, P. (Medicine & Science in Sports & Exercise, 1995)
An experimental group (M = 7, F = 3) wore an elevated-sole shoe and a control group (M = 5, F = 3) wore standard athletic shoes, and both participated in an 8-wk plyometric training program. Remembering that these were small sample groups the following results were demonstrated: - both experimental and control groups improved, none more than the other; - female Ss improved slightly, no group more than the other; and - the male experimental group improved more than the control group. Implication: At best, given the number of Ss, this investigation was a "pilot" research effort. That males differed in the response to strength/power training is in accord with other studies now coming to light. It is possible that the raised sole produces too much overload to provoke an improved training response, particularly in females. The transfer of "shoe-training" benefits to actual activities have to be evaluated before this can be deemed a valuable training alternative.